Does marginal cost pricing of public sector information spur firm growth? - Heli Koski (The Research Institute of the Finnish Economy (ETLA), 2011)
The firm-level data concerning re-users of geographical information (GI) active in architectural and engineering activities and related technical consultancy sector from 15 countries during the year 2000-2007 suggests that the pricing of public sector GI strongly relates to the firms' sales growth. Firms functioning in the countries in which public sector agencies provide fundamental geographical information either freely or at maximum marginal costs have grown, on average, about 15 percent more per annum than the firms in the countries in which public sector GI is priced according to the cost-recovery principle. The difference-in-difference estimations further show that positive growth impact materializes already one year after switching to the marginal cost pricing scheme but a stronger boost to the firm growth takes place with a two year lag. Interestingly, marginal cost pricing has not generated notable growth among the large firms; it has been SMEs benefiting most from cheaper geographical information. It seems credible that switching to marginal cost pricing of public sector information (PSI) substantially lowers SMEs' barriers to enter new market areas in the provision of GI-based products and services.
Keywords: L25; L84; O38; 330; public sector information; pricing; firm growth; technology policy; Geoinformationssystem; Öffentliche Dienstleistung; Unternehmenswachstum; Grenzkostenpreis